Online Learning Management during the Covid-19 Pandemic in Vocational High School - Ahmad Tahalli; Lantip Diat Prasojo (STAI Hubbulwathan Duri, 2021)
Research in this area is focused on 1) analyzing school-based use of online learning management, 2) finding patterns, 3) explaining how online learning management strategies work, 4) identifying both supporting and inhibiting factors. This study employs a qualitative case study methodology. Students and teachers were the primary and secondary sources of information for this study. Observation, interviews, and documentation are used in this study to gather data. To summarize: (1) the concept of online learning management can use WhatsApp to convey information and Google Classroom for learning; (2) the pattern used in school management is to use four steps of management functions; (3) the strategy used in online learning management is to assign tasks and responsibilities based on the abilities and skills of teachers involved in the online learning process; and (4) For those who lack an Android phone and an Internet connection, it can be challenging to connect to the network. Some teachers and students have difficulty effectively navigating and utilizing various forms of media. It is expected that the findings of this study will be used as a guide for online learning in vocational high schools during the pandemic.